Pengaruh Jenis Starter Bakteri Asam Laktat terhadap Produksi Asam Laktat dan Kadar Protein dalam Pembuatan Yoghurt Kacang Hijau (Phaseolus radiatus L.) - Rozana Zuhri (Pendidikan Biologi FKIP UMMY, 2019)
Yoghurt Green beans (Phaseolus radiatus L.) is a dairy product green beans fermented with the help of lactic acid bacteria (LAB). This green bean fermentation of milk has many benefits, among others, to preserve food products, provide texture and taste or flavor of the food product. In addition fermentation with BAL will reduce the unpleasant odors that are not favored by consumers on green bean milk. Work lactic acid bacteria (LAB) in fermented milk can help improve health, for people who suffer from lactose intolerance and can increase the protein content in green beans. As for the purpose of this research was to study the effect of lactic acid bacteria starter to the production of lactic acid and the protein content in the manufacture of yoghurt green beans (Phaseolus radiatus L.).This research was conducted in the laboratory of Biology STKIP Bangko YPM in October-December 2015. In this research, testing tertitrasi total lactic acid and protein content. This study uses a RAL (Complete Random Design). Type starter bacteria used are Lactobacillus bulgaricus, Streptococcus thermophillus and a combination of Lactobacillus bulgaricus with Streptococcus thermophillus. Starter concentration used was 5%. While the research results were analyzed using ANOVA, if the result of variance showed a difference, then followed by a further test DNMRT at the level of 5%. The results of this study indicate that the type of starter significant effect on the protein content of yogurt green beans while total lactic acid is not significant. The combination starter of Lactobacillus bulgaricus and Streptococcus thermophillus with a concentration of 5% which gives the best results the protein content of yogurt green beans that is equal to 14.592%. It can be concluded that this type of mixed starter of Lactobacillus bulgaricus and Streptococcus thermophillus influenced the protein content of yogurt green beans.